Effects of Growth Hormone Replacement on Peripheral Muscle and Exercise Capacity in Severe Growth Hormone Deficiency - Gonzalez, Susana; Sathyapalan, Thozhukat; Javed, Zeeshan; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Objective The aim of this study is to evaluate the effect of growth hormone therapy (rGH) on mitochondrial function on peripheral muscle and to correlate with exercise capacity in subjects with severe adult growth hormone deficiency (GHD). Design Six months, double-blind, randomized, crossover, placebo-controlled trial of subcutaneous rGH in 17 patients with GHD. Measurements Quadriceps muscle biopsies were obtained at baseline, 3 months, and 6 months to measure succinate dehydrogenase (SDH) to assess mitochondrial activity. Exercise capacity was measured with cardiopulmonary exercise testing. Lipids, glycemic parameters, and body fat levels were also measured. Results Serum insulin-like growth factor 1 (IGF1) levels reduced fat mass by 3.2% (p < 0.05) and normalized with rGH in the active phase (p < 0.005). Patients showed an increase in SDH (p < 0.01) from base line that differed between placebo and rGH therapy treatment groups (p < 0.05): those treated by rGH followed by placebo showed a significant increase in SDH (p < 0.001) followed by a decrease, with a significant between group difference at the end of 6 months (p < 0.05). No significant improvements or correlation with exercise capacity was found. Conclusion Short-term rGH for 3 months normalized IGF1 levels, reduced fat mass, and had a significant effect on mitochondrial function, but exercise capacity was unchanged. Clinical Trial Registration Number ISRCTN94165486.